1995
DOI: 10.1207/s15327752jpa6503_11
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics of Hospice Volunteers as Measured by Myers-Briggs Type Indicator

Abstract: A sample of hospice volunteers (n = 99) was administered the Myers-Briggs Type Indicator (Myers & McCaulley, 1985). Frequencies of types observed were compared to population sample (n = 1,105) frequencies. Results indicated that, as a whole, hospice volunteers preferred extraversion over introversion, intuition over sensing, and feeling over thinking. Analysis of four-and two-letter preference combinations also yielded statistically significant differences. Most notably, the sensing-intuitive function appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
1
16
0
4
Order By: Relevance
“…The Myers-Briggs-type personality profiles of hospice volunteers (compared against the typical observed frequency of personality types in the general population) show that hospice volunteers are more apt to be extroverted than introverted, more feeling than thinking, and rely more on intuition EMPATHY AND SOCIAL SUPPORT 21 over sensing (Mitchell & Shuff, 1995). 1 Hospice volunteers also tend to report themselves as being low in communication anxiety and high in empathy (Wilkinson & Wilkinson, 1986).…”
Section: Personal Characteristics Of Hospice Volunteersmentioning
confidence: 97%
“…The Myers-Briggs-type personality profiles of hospice volunteers (compared against the typical observed frequency of personality types in the general population) show that hospice volunteers are more apt to be extroverted than introverted, more feeling than thinking, and rely more on intuition EMPATHY AND SOCIAL SUPPORT 21 over sensing (Mitchell & Shuff, 1995). 1 Hospice volunteers also tend to report themselves as being low in communication anxiety and high in empathy (Wilkinson & Wilkinson, 1986).…”
Section: Personal Characteristics Of Hospice Volunteersmentioning
confidence: 97%
“…Similarly, volunteers tend to have a more empathic personality than paid employees (Mitani, 2014). Earlier research (Mitchell & Shuff, 1995) even found that volunteers were more likely to display traits that are related to feelings (e.g., agreeableness, associated with warmth: Aaker, 1997;Elshaug & Metzer, 2001) than to thoughts (e.g., conscientiousness, more related to competence: Kervyn et al, 2012).…”
Section: Volunteering Versus Paid Staffmentioning
confidence: 95%
“…A hospice önkéntesség erősen szociális természete és nagyfokú érzelmi bevonódást igénylő jellege miatt nem meglepő, hogy az önkénteseket általában magasabb empátia és érzelmi válaszkészség, gondoskodó attitűd és alacsonyabb szorongás jellemzi, mint önkéntes munkát nem végző társaikat (Lamb és mtsai, 1985). Az ide vonatkozó kutatások többsége (Briggs, 1987;Lafer, 1989;Mitchell & Shuff, 1995;Paradis & Usui, 1987) érzelmek magasabb fokú kontrollja, mások (gyakran erőteljes) érzelmi reakcióinak higgadt kezelése jellemzi őket, ami a racionális helyzetértelmezés révén hatékony megküzdési stratégiák alkalmazásához vezethet. Ugyanezen vizsgálatban az empátia tekintetében is magasabb értékeket találtak az önkénteseknél, főként a kognitív empátia mutatóiban mutatkozik különbség: magasabb empátiás törődés (együttérzés másokkal és törődés mások problémáival) és a szociális nézőpontváltásra való képesség (más személyek nézőpontjából tekinteni a dolgokat) jellemzi őket (lásd még Egbert & Parrott, 2003).…”
Section: A Hospice öNkéntesek Személyiségeunclassified